2007
DOI: 10.1002/bem.20327
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HSP72 after ELF‐EMF exposure in three cell lines

Abstract: It has been reported that magnetic fields with flux densities ranging from microT to mT are able to induce heat shock factor, HSP72 mRNA or heat shock proteins in various cells. In this study we investigated changes in the HSP72 mRNA transcription level in three cell lines (HL-60, H9c2, and Girardi heart cells) and in the intracellular HSP72 protein content in two cell lines (HL-60 and Girardi heart cells) after treatment schemes using electromagnetic fields with a flux density of 2 microT to 4 mT, a frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Using high-throughput analysis, we found that genome-wide expression levels in MCF10A human breast epithelial cells were not changed by exposure to ELF-MFs. To confirm these results, we performed sqRT-PCR on six genes selected from the microarray analysis that exhibited statistically non-significant trends for expression changes; the follow-up results confirmed those of the Previous studies reported that ELF-MF exposure could affect transcription levels in vitro of several immediate-response genes [8], [19][21]. These studies, however, only looked at a few genes and their results require further confirmation before firm conclusions can be drawn.…”
Section: ⅳ Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Using high-throughput analysis, we found that genome-wide expression levels in MCF10A human breast epithelial cells were not changed by exposure to ELF-MFs. To confirm these results, we performed sqRT-PCR on six genes selected from the microarray analysis that exhibited statistically non-significant trends for expression changes; the follow-up results confirmed those of the Previous studies reported that ELF-MF exposure could affect transcription levels in vitro of several immediate-response genes [8], [19][21]. These studies, however, only looked at a few genes and their results require further confirmation before firm conclusions can be drawn.…”
Section: ⅳ Discussionsupporting
confidence: 59%
“…Martínez et al reported that ELF-MF could stimulate proliferative activity in neuronal cells by triggering MAPK-ERK1/2 signaling [7]. It has been also reported that electromagnetic fields (EMF) transiently influence the transcript level of genes related to apoptosis and the cell cycle [8], [9]. However, in vitro studies failed to demonstrate any biological effects of ELF-MFs [10][13].…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…On the other hand, they suggested that short-term exposure may be beneficial since it induced protection during subsequent hypoxia or UV radiation. Gottwald et al [2007] observed that 1 mT field exposure for 15 min resulted in an increase in HSP72 mRNA, but the hsp70 protein level did not increase. They argued that transcriptional activation of HSP72 gene is independent of protein synthesis.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies suggested that there is a possible association between ELF-MFs and malignancies in childhood and adulthood such as leukemia and nervous system tumors as well as cardiovascular and neurological disorders [Wertheimer and Leeper, 1979;IARC, 2002;Håkansson et al, 2003;Draper et al, 2005;Davanipour et al, 2007]. A number of in vivo and in vitro investigations have shown a possible co-promoter capacity of ELF-MFs on tumor growth as well as the potential effects elicited by ELF-MFs on various cellular functions [Crumpton and Collins, 2004;Simkó , 2004;Santini et al, 2005;Wolf et al, 2005;Berg and Berg, 2006;Frahm et al, 2006;Lisi et al, 2006;Palumbo et al, 2006;Gottwald et al, 2007]. Unfortunately, the biological mechanisms by which these physical agents can be involved in a possible tumor-promoting or tumor-initiating action are still unclear.…”
mentioning
confidence: 99%